Dinamika Parpol Tentang Wacana Perubahan Sistem Pemilu 2024 dalam Perspektif Demokrasi - Kusuma Wijaya (Jurnal Hukum dan Sosial Politik, 2023)
Democracy as the basis of state life allows recognition that, at the last level, the people regulate the main issues that concern their lives, including evaluation of state policies because they determine their lives. ) to the Constitutional Court regarding Law Number 7 of 2017 concerning General Elections regarding an open proportional system. The purpose of this study is to examine the closed proportional system discourse which is suitable to be reapplied in the 2024 General Election from a democratic perspective. The research methodology used is a normative juridical approach. Implications A closed or open proportional system cannot be said to be ideal for several reasons, namely, (1) In an open proportional system many candidates engage in money politics by secretly distributing money to the public. However, in a closed system, one cannot guarantee that this practice will be prevented and gain internal support within one's party. (2) Very suitable, each party can provide the best candidate in accordance with the development and progress of community needs. However, it is possible for the party to create other objectives for its own interests. (3) The principle of open proportionality, anyone who has fame and popularity but without proper background can easily be elected to a seat in parliament.